Preoperative C-reactive protein as a predictor of postoperative acute kidney injury in patients undergoing coronary artery bypass grafting. (May 2021) - Mohamed, Walid; Asimakopoulos, George
C-reactive protein is a well-known marker of inflammation and may be preoperatively elevated in the absence of infection in adult cardiac surgery patients, indicating a baseline inflammatory process. We conducted a literature search to assess the available evidence on whether there is an association between preoperative C-reactive protein and acute kidney injury after coronary artery bypass grafting. Included only were observational studies which investigated this association. We excluded abstracts, case reports, animal studies and articles in languages other than English. Altogether, 199 papers were retrieved from the search strategy reported, of which 6 studies were included in the final review. The study types, publication details, patient groups and key results are tabulated. A qualitative assessment of these papers was conducted. We conclude that there is some evidence to support the association between high preoperative C-reactive protein level and postoperative acute kidney injury and complications after coronary artery bypass grafting. Owing to variability in acute kidney injury definitions and C-reactive protein levels for different cohorts in the observational studies reviewed, it is unclear from current evidence what serum C-reactive protein cut-off level is significantly associated with postoperative acute kidney injury. Further evidence is needed to investigate whether raised preoperative C-reactive protein in the absence of an infective cause could have a role in risk prediction models for cardiac surgery–associated acute kidney injury.